Design and Testing of Holagen Incandescent Lamp-Based Corn Drying Cabinet to Improve Efficiency and Cleanliness of the Processing Process - Purnomo, Bagas Prasetyo; Fzahruddin, A’rasy (Indonesian Journal of Microbiology, 2024)
Indonesia is a tropical country with entrepreneurs engaged in maize cultivation, most of whom live in rural areas. The corn processing process is heavily reliant on sunshine, however owing to the unpredictable environment and sunlight, which is less effective and hygienic in carrying out the corn drying process, the operation is hampered. As a result, a drying cabinet is created that uses heat from electricity and is specifically intended to accelerate the drying process. This corn drying rack employs incandescent lamps, including bulbs and holagen lamps. In addition, the number of drying racks is identified in order to assess the drying cabinet's capacity for work. After testing the tool with various blower speeds (15,000, 10,000, and 5,000 RPM), the electrical power utilized is 120 watts, which includes 50 watts of bulb/halogen lamp power, 40 watts of heated glass, and 30 watts of blower power. So it is known that holagen incandescent lamps are more successful at distributing work evenly on the shelf within 30 minutes, which can save drying time by 20% to 30%.